Nectria haematococca causing root rot in olive greenhouse plants - D. Barreto; S. Babbitt; M. Gally; B. A. Pérez (RIA: Revista Investigaciones Agropecuarias)
This is the first report of Nectria haematococca Berk. & Br. in Argentina. Itwas isolated from 8 to 12 month greenhouse olive Olea europaea L. plants. Theanamorph, Fusarium solani (Mart.) Sacc., was frequently isolated while theteleomorph was rare in culture. Perithecia developed on plated olive root segmentsand around the PDA medium. Two isolates of F. solani produced orange perithecia,which remained immature for several months. A third isolate developed peritheciacontaining asci with 2-cell light brown and longitudinally striated ascospores, atmaturity. Young olive plants inoculated with F. solani showed leaf browning,root rot, wilting and plant death. Controls remained healthy. The presence ofthe sexual stage is responsible for the genetic variability of this pathogen